HAMBATAN YANG DIHADAPI WANITA DALAM MENJALANKAN KEWIRAUSAHAAN (study kasus di Dusun Rejoso Desa Rejosopinggir) - Vebyyanti, Silvya Eka; Susilowati, Lina (Jurnal Konstanta, 2022)
This study aims to determine the factors that influence women in running entrepreneurship in Rejoso Hamlet, Rejosopinggir Village, namely the first is the independence factor, the second is the capital factor, the third is the educational factor, and the fourth factor is the emotional factor. The research method used is descriptive qualitative research method by conducting interviews and direct observations. The subjects in this study were women who had run entrepreneurship for at least 4 years as many as 5 people. The data collection techniques were carried out by interviewing informants directly about the obstacles women face in running entrepreneurship in Rejoso Hamlet, Rejosopinggir Village. The obstacles faced by women in running entrepreneurship are the first is the lack of capital, the second is the lack of ability or skills, the third is the lack of support, and the fourth is the fear of taking risks. Keywords: entrepreneurship, women, capital, skill, risk